2016
DOI: 10.1007/s11077-016-9248-y
|View full text |Cite
|
Sign up to set email alerts
|

Toward a processual understanding of policy integration

Abstract: The role of policy integration in the governance of cross-cutting policy problems has attracted increasing scholarly attention in recent years. Nevertheless, the concept of policy (dis)integration is still under theorized, particularly regarding its inherent processual nature. The main argument of this paper is that policy integration should be understood as a process that entails various elements that do not necessarily move in a concerted manner but may develop at different paces or even in opposite directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
352
0
19

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 323 publications
(430 citation statements)
references
References 93 publications
5
352
0
19
Order By: Relevance
“…As Candel and 249 Biesbroek (2016) carefully suggest, policy integration is a process and in the two case studies, five process-based characteristics (see Figure 8-1) influenced integration and CSA. Furthermore, the study found that at the community-level there was less disparity between the two, at the national level adaptation and mitigation measures in the two cases were treated differently within policy, practice and funding.…”
mentioning
confidence: 84%
“…As Candel and 249 Biesbroek (2016) carefully suggest, policy integration is a process and in the two case studies, five process-based characteristics (see Figure 8-1) influenced integration and CSA. Furthermore, the study found that at the community-level there was less disparity between the two, at the national level adaptation and mitigation measures in the two cases were treated differently within policy, practice and funding.…”
mentioning
confidence: 84%
“…The table operationalizes the sub-dimensions by setting ideal-type values (bold and italicized) that allow us to assess whether the EU governance of food security changed during and following the food price spikes (Sections 3 and 4). Table 1 Dimensions of policy integration (adopted from Candel and Biesbroek 2016;Candel 2017a) Lack of policy integration The first dimension of policy integration consists of the policy frame within a governance system. Policy frame is a frequently used concept in public policy studies and generally refers to policy stakeholders' competing or dominant problem definitions of a particular societal issue (e.g., Schön and Rein 1994;Roggeband and Verloo 2007).…”
Section: A Policy Integration Framework For Assessing Eu Food Securitmentioning
confidence: 99%
“…Governments and international organizations have taken an increasing interest into developing integrated policy strategies (IPSs) in the new millennium (Bogdanor 2005;United Nations 2015;Candel and Biesbroek 2016;Cejudo and Michel 2017). Recognition that many of today's most pressing societal problems crosscut the boundaries of traditional jurisdictions, the effects of (too) successful New Public Management reforms, and the subsequent emergence of holistic governing paradigms, such as joined-up-governance and whole-of-government, have, among other causes, made pursuing policy integration into the quest for the philosopher's stone (Rhodes 2000;Peters 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Uittenbroek 2014) or 'cooperation' and 'coordination ' (e.g. Geerlings and Stead 2003), 1 they are adopted to pursue a set of integrated goals by a polity as a whole (Metcalfe 1994;Candel and Biesbroek 2016). IPSs are here defined as explicit governmental attempts to address one or more crosscutting concerns -such as food insecurity, climate change, or homeland security -in a holistic manner and for that reason prescribe concerted policy-making efforts across sectors and, possibly, levels within a polity.…”
Section: Introductionmentioning
confidence: 99%